Wastewater characteristics from tofu processing facilities in Banda Aceh - M. FAISAL; FARID MULANA; POCUT N. ALAM; HIROYUKI DAIMON (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Tofu is a very favorite food in Asian countries such Indonesia, and is gaining popularity among west countries as well, due to the associated health benefits and its acceptable price. Tofu which is produced by grinding of soy bean produces high of amount wastewater, and is considered as one of the most polluting food-industrial effluent due to its high values of organic pollutants. This paper analyzed  some pollutants parameter discharged from tofu industries in Banda Aceh. The parameter of BOD, COD, MLSS, PO4-P NH3-N, Turbidity and pH were analyzed based on the standard method for the examination of water and wastewater, approved by the EPA. The COD and BOD of wastewater from tofu processing facilities in Banda Aceh is ranging from 5000-8500 and 3500-4500 mg/L, respectively. Site investigation showed that in Banda aceh city, the tofu waste has been disposed into the environment without any treatment, causing bad odours and pollution of the surface, ground water and river